2009
DOI: 10.1021/es803556w
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater Pollution by Perfluorinated Surfactants in Tokyo

Abstract: Perfluorinated surfactants (PFSs) in groundwater were analyzed to reveal their distribution and sources. Sixteen groundwater and spring samples were collected from the Tokyo metropolitan area, and nine PFSs, including perfluorooctane-sulfonate (PFOS) and perfluorooctanoate (PFOA), were analyzed by liquid chromatography-tandem mass spectrometry. A column test using artificial street runoff was also performed to study their behavior. PFSs were detected in all groundwater samples, some at concentrations comparabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
85
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(94 citation statements)
references
References 31 publications
7
85
1
1
Order By: Relevance
“…Przykładem punktowego źródła emisji związków perfluorowanych może być np. użytkowanie pian gaśniczych [44], zrzut ście-ków komunalnych i przemysłowych [4]. Badania Schultza wykazały obecność PFOA i PFOS w ściekach surowych i oczyszczonych w 10 oczyszczalniach ścieków w USA [57].…”
Section: Zagrożenia Wynikające Z Obecności Pfcs W śRodowiskuunclassified
“…Przykładem punktowego źródła emisji związków perfluorowanych może być np. użytkowanie pian gaśniczych [44], zrzut ście-ków komunalnych i przemysłowych [4]. Badania Schultza wykazały obecność PFOA i PFOS w ściekach surowych i oczyszczonych w 10 oczyszczalniach ścieków w USA [57].…”
Section: Zagrożenia Wynikające Z Obecności Pfcs W śRodowiskuunclassified
“…[33] Murakami et al surveyed sources of perfluorocarboxylates (PFCAs) in groundwater in Tokyo using differences in PFS compositions among sources and suggested that surface runoff contributed to between 16 and 46% of PFCAs. [10] Consistent findings show that non-point sources play important roles in contamination by PFCAs, but not by perfluoroalkyl sulfonates (PFASs). [24,32,33] The entry of PFSs, especially PFCAs, from surface runoff into waters is a matter of concern.…”
Section: Introductionmentioning
confidence: 99%
“…potassium salt of PFOS, 570 mg L À1 at 24-258C; PFOA, 9500 mg L À1 at 258C), [3,4] bioaccumulative, [5,6] and environmentally persistent. Owing to these features, PFSs have been ubiquitously detected in surface water, [7][8][9] groundwater, [10] seawater, [11][12][13][14] drinking water, [15] aquatic organisms, [16,17] and humans. [18,19] As PFSs are suspected of being carcinogenic, of being chronic and reproductive toxicants, and of having adverse effects on humans and other animals, [20][21][22] concerns about PFSs are increasing.…”
Section: Introductionmentioning
confidence: 99%
“…However, the highest thermal stability of C-F bond [1] makes PFAAs persistent pollutants that they have been globally detected in soil [2], sediment [3], surface water [4], groundwater [5], seawater [6], landfill leachate [7], indoor dust [8] etc., as well as human beings [9]. Because of the global distribution and similar property with persistent organic pollutants (POPs), perfluorooctane sulfonic acid (PFOS) and the related substances were newly added as Annex B substance of POPs under the Stockholm Convention in 2009 [10].…”
Section: Introductionmentioning
confidence: 99%